UNSTEADY MIXED CONVECTION IN A POROUS MEDIA FILLED LID-DRIVEN CAVITY HEATED BY A SEMI-CIRCULAR HEATERS - Rahman, Md Mustafizur; Öztop, Hakan Fehmi; Saidur, Rahman; Mekhilef, Saad; Al-Salem, Khaled (Vinca Inst Nuclear Sci, 2015)
A computational study has been performed on natural convection heat transfer and fluid flow in a porous media filled enclosure with semi-circular heaters by using finite element method. The ceiling of the cavity moves with a constant velocity and it is insulated. Vertical walls temperature is lower than that of heaters. Results are presented via streamlines, isotherms, average Nusselt numbers, and cross-sectional velocity for different governing parameters such as Richardson and Darcy numbers, and dimensionless time. It is observed that both circulation of the flow and heat transfer is strongly affected with time increment and Darcy number inside the cavity.
Keywords: porous media; lid-driven cavity; mixed convection; curvilinear heater